Pericardial fat and its influence on cardiac diastolic function - Vera H. W. de Wit-Verheggen; Sibel Altintas; Romy J. M. Spee; Casper Mihl; Sander M. J. van Kuijk; Joachim E. Wildberger; Vera B. Schrauwen-Hinderling; Bas L. J. H. Kietselaer; Tineke van de Weijer (Cardiovascular Diabetology, 2020)
Abstract Background Pericardial fat (PF) has been suggested to directly act on cardiomyocytes, leading to diastolic dysfunction. The aim of this study was to investigate whether a higher PF volume is associated with a lower diastolic function in healthy subjects. Methods 254 adults (40–70 years, BMI 18–35 kg/m2, normal left ventricular ejection fraction), with (a)typical chest pain (otherwise healthy) from the cardiology outpatient clinic were retrospectively included in this study. All patients underwent a coronary computed tomographic angiography for the measurement of pericardial fat volume, as well as a transthoracic echocardiography for the assessment of diastolic function parameters. To assess the independent association of PF and diastolic function parameters, multivariable linear regression analysis was performed. To maximize differences in PF volume, the group was divided in low (lowest quartile of both sexes) and high (highest quartile of both sexes) PF volume. Multivariable binary logistic analysis was used to study the associations within the groups between PF and diastolic function, adjusted for age, BMI, and sex. Results Significant associations for all four diastolic parameters with the PF volume were found after adjusting for BMI, age, and sex. In addition, subjects with high pericardial fat had a reduced left atrial volume index (p = 0.02), lower E/e (p < 0.01) and E/A (p = 0.01), reduced e′ lateral (p < 0.01), reduced e′ septal p = 0.03), compared to subjects with low pericardial fat. Conclusion These findings confirm that pericardial fat volume, even in healthy subjects with normal cardiac function, is associated with diastolic function. Our results suggest that the mechanical effects of PF may limit the distensibility of the heart and thereby directly contribute to diastolic dysfunction. Trial registration NCT01671930